THE IMPLEMENTATION OF EMPLOYEEâS PERFORMANCE ASSESSMENT POLICY BASED ON GOVERNMENT REGULATION NO. 46/2011 THROUGH THE IMPROVEMENT OF APPARATUS COMPETENCY IN TRAINING AND EDUCATION INSTITUTION IN CENTRAL JAVA PROVINCE - Riagustrianingsih, Endang (The Journal of Educational Development, 2015)
In order to improve the accountability of public sector performance, government is challenged to make an accountability system based on performance by creating an effective performing management model. The pressure of government organization either central or district for fixing their performance pushes the building of public sector management organizational system based on performance-based management. This change is done for implementing the bureaucracyâs role and function exactly, quickly, and consistently for getting the utilization based on the constitutionâs mandate. The bureaucracyâs reformation is expected to change the mind of the civil public servants from wanting to be served to be the servant (guardian) that makes the society happy; and from relaxing culture, laziness, and undisciplined to be the hard-working culture, be spirit, innovative, creative, and discipline. In implementing the advising of civil public servant based on the performance achievement and career system through the working performance achievement, working performance is needed to be assessed. This is based on what is being mandated by the law No. 46 Year 2011 about civil public servantsâ working performance assessment.By doing this, they can serve appropriately like the expected competency.